2020
DOI: 10.1080/07421656.2020.1739599
|View full text |Cite
|
Sign up to set email alerts
|

Art Therapy and the Malnourished Brain: The Development of the Nourishment Framework

Abstract: Art therapy can be particularly successful in addressing the specific needs of individuals struggling with anorexia nervosa (AN) through the use of the creative process. This article provides an understanding of the effect of malnourishment on the brain for individuals with AN and discusses how their unique needs can be met through the application of the Nourishment Framework. The Nourishment Framework is a structured treatment approach that utilizes the individual components of the Expressive Therapies Contin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In an artwork titled ‘Imagine Me Beyond What You See’, art was used by the International Association of Eating Disorder Professionals to ensure integration and acceptance in EDs; here art was a catalyst for sharing recovery stories regarding EDs, personal and collective bodily experiences, and raising awareness of EDs and body image (Misluk-Gervase 2020). A case study using the creative process to create a nutritional framework for individuals with AN reported that expressive art therapy can be particularly successful in meeting the special needs of individuals struggling with AN (Misluk-Gervase 2021). In a compilation of 32 studies from 1987 and 2012 related to psychosomatic disorders, EDs and relevant crises, only 2 were related to art psychotherapy in EDs; these relevant studies (Frisch, Franko, and Herzog 2006; Rehavia-Hanauer 2003) discuss the measurement of the effectiveness of art therapy for EDs, emphasising the limited number of empirical studies (Holmqvıst and Persson 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In an artwork titled ‘Imagine Me Beyond What You See’, art was used by the International Association of Eating Disorder Professionals to ensure integration and acceptance in EDs; here art was a catalyst for sharing recovery stories regarding EDs, personal and collective bodily experiences, and raising awareness of EDs and body image (Misluk-Gervase 2020). A case study using the creative process to create a nutritional framework for individuals with AN reported that expressive art therapy can be particularly successful in meeting the special needs of individuals struggling with AN (Misluk-Gervase 2021). In a compilation of 32 studies from 1987 and 2012 related to psychosomatic disorders, EDs and relevant crises, only 2 were related to art psychotherapy in EDs; these relevant studies (Frisch, Franko, and Herzog 2006; Rehavia-Hanauer 2003) discuss the measurement of the effectiveness of art therapy for EDs, emphasising the limited number of empirical studies (Holmqvıst and Persson 2011).…”
Section: Introductionmentioning
confidence: 99%